Catalytic enantioselective 1,3-alkyl shift in alkyl aryl ethers: efficient synthesis of optically active 3,3 '-diaryloxindoles - Gade, Amol B.; Bagle, Pradip N.; Shinde, Popat S.; Bhardwaj, Vipin; Banerjee, Subhrashis; Chande, Ajit; Patil, Nitin T. (Angewandte Chemie-International Edition, 2018)
Reported is the first organocatalytic asymmetric 1,3-alkyl shift in alkyl aryl ethers for the synthesis of chiral 3,3'-diaryloxindoles using a chiral Bronsted acid catalyst. Preliminary results showed that each enantiomer of the 3,3'-diaryloxindole, and a racemic mixture, showed different antiproliferative activities against HeLa cell lines by using an MTT assay.